1990
DOI: 10.1093/carcin/11.7.1237
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of DNA excision repair and nucleosomal unfolding in poly (ADP-ribose)-depleted mammalian cells

Abstract: The repair of DNA damage in eukaryotic cells is closely coupled with local changes of chromatin structure such that newly synthesized repair patches transiently appear in 'free' DNA domains with increased accessibility to enzymatic and chemical probes. We have isolated these domains from mammalian cells repairing bulky DNA adducts. During the first 3 h of repair, excision of adducts occurred exclusively in free DNA and was closely linked with the appearance of newly synthesized repair patches. Following deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These observations, together with the data fromour current study (Figures 2 and 3), may begin to clarify earlier observations showing a significant increase in the accessibility of 3'-OH primer sites to DNA polymerase in nuclei preincubated with NAD (Mathis & Althaus, 1990;Roberts et al, 1974). The ability of NAD to release this template restriction and expose DNA primer sites in chromatin has been observed to vary during the cell cycle (Roberts et al, 1974).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations, together with the data fromour current study (Figures 2 and 3), may begin to clarify earlier observations showing a significant increase in the accessibility of 3'-OH primer sites to DNA polymerase in nuclei preincubated with NAD (Mathis & Althaus, 1990;Roberts et al, 1974). The ability of NAD to release this template restriction and expose DNA primer sites in chromatin has been observed to vary during the cell cycle (Roberts et al, 1974).…”
Section: Discussionsupporting
confidence: 90%
“…Immunochromatography with antibodies to poly(ADP-ribose) has revealed that chromatin regions adjacent to DNA strand breaks in HeLa cells as well as in polyoma-and SV40-infected cells possess a high concentration of poly(ADP-ribosy1)ated proteins (Baksi et al, 1987;Thraves et al, 1985). In this regard, Mathis and Althaus (1990) demonstrated an influence of chromatin structure on DNA repair while studying the inhibition of repair with chemical inhibitors of PADPRP. An open chromatin structure became apparent during the repair of bulky alkylation adducts.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism might act in vivo as a catalyst of nucleosome unfolding, by transiently displacing histones from DNA and hence facilitating DNA transactions by increasing template accessibility. In poly(ADP-ribose)-depleted cells, nucleosome unfolding accompanying the repair of bulky DNA adducts as well as removal of such lesions are severely impaired (Mathis and Althaus 1990).…”
Section: Modulation Of Chromatin Structurementioning
confidence: 99%
“…Not surprisingly, the covalent attachment of ADP-ribose (two negative charges per nucleotide) polymers to an acceptor molecule leads to the shuttling off, or release, of this protein from the helical phosphodiester backbone of DNA (20) (one negative charge per nucleotide). Further, as a result of this ionic repulsion between ADP-ribose polymers and DNA, chromatin structure and function may become uncoupled (21). This uncoupling of chromatin structure and function may directly alter the physiological course of DNA replication (22), DNA recombination (23), gene expression (24)(25)(26), DNA base excision repair (27,28), and cell survival or apoptosis (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%